2017
DOI: 10.1002/cmr.b.21362
|View full text |Cite
|
Sign up to set email alerts
|

Capacitor re‐design overcomes the rotation rate limit of MACS resonators

Abstract: The magic angle coil spinning (MACS) technique has provided a breakthrough in enhancing sensitivity in magic angle spinning (MAS) NMR. However, efforts in improving the MACS detector for higher spinning speeds have been lacking. One published MACS construction technique is to solder a handwound solenoidal coil to a commercial non-magnetic capacitor and subsequently centering the detector inside the MAS rotor. An alternative method to realize these detectors is by using MEMS fabrication at the wafer scale, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…The maximum reported gain in sensitivity from these inserts was only about 3; the final assembly was done manually and therefore may also be prone to imbalances. In a recent paper, 12 we have confirmed that, for Q-factor values of the entire MACS micro-resonator chain higher than 20, the wireless coupling efficiency η between the micro-resonator and the MAS probehead coil exceeds 90%. Given the fact that typical values for the quality factor of the micro-coil are around 50, 13 this reduces the requirement on the microfabricated capacitor Q-factor to around 33, achieving a reasonable compromise in signal transfer efficiency between the microfabricated MACS insert and the MAS probehead coil.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…The maximum reported gain in sensitivity from these inserts was only about 3; the final assembly was done manually and therefore may also be prone to imbalances. In a recent paper, 12 we have confirmed that, for Q-factor values of the entire MACS micro-resonator chain higher than 20, the wireless coupling efficiency η between the micro-resonator and the MAS probehead coil exceeds 90%. Given the fact that typical values for the quality factor of the micro-coil are around 50, 13 this reduces the requirement on the microfabricated capacitor Q-factor to around 33, achieving a reasonable compromise in signal transfer efficiency between the microfabricated MACS insert and the MAS probehead coil.…”
Section: Introductionsupporting
confidence: 61%
“…Table 1 provides a comprehensive overview of the single resonant MACS inserts reported so far: the initial MACS report 1 realized using a handwound coil and a discrete capacitor, an alternative MACS version from the same group based on a printed coil, the capacitor being realized through the distributed capacitance between the windings, 3 and the two types of wirebonded coils, one with on-chip interdigitated capacitors, 2 the other with the parallel plate on-chip capacitor. 12 A first inspection of this table shows that, except for the structure built using interdigitated capacitors, the other three devices show rather similar performance. The relatively lower performance in terms of spectral resolution exhibited by the printed coil MACS might be due to the properties of its constitutive materials, however it is worth noting that this device has the least eddy current heating.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation